Functional specificity of sex pheromone receptors in the cotton bollworm Helicoverpa armigera. - Yang Liu (PLoS ONE, 2013)
Male moths can accurately perceive the sex pheromone emitted from conspecific females by their highly accurate and specific olfactory sensory system. Pheromone receptors are of special importance in moth pheromone reception because of their central role in chemosensory signal transduction processes that occur in olfactory receptor neurons in the male antennae. There are a number of pheromone receptor genes have been cloned, however, only a few have been functionally characterized. Here we cloned six full-length pheromone receptor genes from Helicoverpa armigera male antennae. Real-time PCR showing all genes exhibited male-biased expression in adult antennae. Functional analyses of the six pheromone receptor genes were then conducted in the heterologous expression system of Xenopus oocytes. HarmOR13 was found to be a specific receptor for the major sex pheromone component Z11-16:Ald. HarmOR6 was equally tuned to both of Z9-16: Ald and Z9-14: Ald. HarmOR16 was sensitively tuned to Z11-16: OH. HarmOR11, HarmOR14 and HarmOR15 failed to respond to the tested candidate pheromone compounds. Our experiments elucidated the functions of some pheromone receptor genes of H. armigera. These advances may provide remarkable evidence for intraspecific mating choice and speciation extension in moths at molecular level.